2019
DOI: 10.3892/ijmm.2019.4087
|View full text |Cite
|
Sign up to set email alerts
|

NR2F2 loss‑of‑function mutation is responsible for congenital bicuspid aortic valve

Abstract: congenital bicuspid aortic valve (BAV) represents the most common type of cardiac birth defect affecting 0.4-2% of the general population, and accounts for a markedly increased incidence of life-threatening complications, including valvulopathy and aortopathy. Accumulating evidence has demonstrated the genetic basis of BAV. However, the genetic basis for BAV in the majority of cases remains to be elucidated. In the present study, the coding regions and splicing donors/acceptors of the nuclear receptor subfamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…NR2F2 is similarly expressed in the brain, but more broadly in the ovary, endometrium, spleen as well as in several other tissues including the heart, kidney and gastrointestinal organs like the stomach, colon, duodenum, and esophagus (Lin et al 2011). Pathogenic mutation in this gene has been implicated in cardiovascular disorders including congenital heart defects (Al Turki et al 2014;Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…NR2F2 is similarly expressed in the brain, but more broadly in the ovary, endometrium, spleen as well as in several other tissues including the heart, kidney and gastrointestinal organs like the stomach, colon, duodenum, and esophagus (Lin et al 2011). Pathogenic mutation in this gene has been implicated in cardiovascular disorders including congenital heart defects (Al Turki et al 2014;Wang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The well-established environmental factors underlying CHD include maternal conditions (such as innutrition, viral infection and endocrine disorder) and exposures to toxic chemicals, therapeutic drugs, or ionizing radiation during pregnancy (Patel and Burns, 2013). However, increasing studies underscore the genetic defects underpinning CHD, and variations in over 70 genes, encompassing those encoding transcription factors, signaling molecules, and sarcomeric proteins, have been involved in CHD (Bashamboo et al, 2018;Cantù et al, 2018;Jaouadi et al, 2018;Li et al, 2018a,c;Lombardo et al, 2018;Manheimer et al, 2018;Pierpont et al, 2018;Razmara and Garshasbi, 2018;Stephen et al, 2018;Xu et al, 2018;Yu Z et al, 2018;Alankarage et al, 2019;Gao et al, 2019;Kalayinia et al, 2019Kalayinia et al, , 2020Ma et al, 2019;Wang J et al, 2019, Wang Z et al, 2019Watkins et al, 2019;Zhu et al, 2019;Faucherre et al, 2020;Shabana et al, 2020;Zhao et al, 2020). Among the recognized CHD-causative genes, the majority code for cardiac transcription factors, encompassing TBX5, GATA4, and NKX2-5 (Li and Yang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Association of COUP-TFII to CHD was later confirmed by other groups [118][119][120][121][122]. Interestingly, deletion of 15q is not the only possible mutation happening in CHD in the COUP-TFII locus but single point missense mutations of the NR are sufficient to induce the pathogenic phenotype [120,122]. Recently, hyper-methylation of the promoter has been associated with the development of the double-outlet right ventricle [119], and a reduction in COUP-TFII expression, a consequence of polymorphisms or single point mutations of FOXC2, causes varicosity and valve failure in veins [123].…”
Section: Cardiovascular Diseasesmentioning
confidence: 64%
“…Mapping a 5.8 Mb deletion in a patient with CHD, Nakamura et al [117] identified COUP-TFII as a putative candidate gene. Association of COUP-TFII to CHD was later confirmed by other groups [118][119][120][121][122]. Interestingly, deletion of 15q is not the only possible mutation happening in CHD in the COUP-TFII locus but single point missense mutations of the NR are sufficient to induce the pathogenic phenotype [120,122].…”
Section: Cardiovascular Diseasesmentioning
confidence: 81%